2016
DOI: 10.3389/fimmu.2016.00396
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Lipid IgG Antibodies Are Produced via Germinal Centers in a Murine Model Resembling Human Lupus

Abstract: Anti-lipid IgG antibodies are produced in some mycobacterial infections and in certain autoimmune diseases [such as anti-phospholipid syndrome, systemic lupus erythematosus (SLE)]. However, few studies have addressed the B cell responses underlying the production of these immunoglobulins. Anti-lipid IgG antibodies are consistently found in a murine model resembling human lupus induced by chlorpromazine-stabilized non-bilayer phospholipid arrangements (NPA). NPA are transitory lipid associations found in the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 36 publications
3
30
0
Order By: Relevance
“…This work showed, for the first time, promazine as a drug that can elicit a lupus-like disease in mice, as it had also been demonstrated before in humans [ 31 , 32 ]. Promazine-induced lupus-like disease was similar to that disease already described for chlorpromazine and Mn 2+ , because promazine also induces formation of NPA on liposomes like chlorpromazine or Mn 2+ ; in fact, we have demonstrated that these lipid arrangements, NPA, are responsible for inducing the disease [ 4 , 5 , 25 ].…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This work showed, for the first time, promazine as a drug that can elicit a lupus-like disease in mice, as it had also been demonstrated before in humans [ 31 , 32 ]. Promazine-induced lupus-like disease was similar to that disease already described for chlorpromazine and Mn 2+ , because promazine also induces formation of NPA on liposomes like chlorpromazine or Mn 2+ ; in fact, we have demonstrated that these lipid arrangements, NPA, are responsible for inducing the disease [ 4 , 5 , 25 ].…”
Section: Discussionsupporting
confidence: 73%
“…It is possible that miR-155-5p underexpression leads to AICDA activation in the three murine lupus-like models, mainly due to the known production of specific IgG-class antibodies against NPA in all of these models. Also, it is highly correlated with the higher gene expression related to exogenous antigen presentation and antibody production, as previously found through RNA arrays and confocal microscopy in the murine lupus-like models [ 7 , 25 ].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Financially, the global sales revenue for all monoclonal antibody products was nearly US$75 billion in 2013, and expected to reach $125 billion by 2020. This unprecedented attraction to antibodies originates from the remarkable structural flexibility of these proteins to selectively recognize different antigen classes such as proteins, carbohydrates and lipids and challenging haptens like pharmaceutical small molecules, pesticides and even biomarkers that can contribute to the potential detection of life on other planets like Mars [61,62]. Antibodies not only represent potential therapeutics but can be implemented in diverse bespoke applications such as immunodiagnostics, biosensors, photothermal therapies and nanoparticle conjugation for drug delivery.…”
Section: Impact Of Drug-delivery Systems In Biotherapeutics Developmentsmentioning
confidence: 99%
“…To increase the immunogenic response to small proteins and peptides, they are often conjugated to or incorporated into other proteins and/or biomaterials (11). Although there are some biomaterials that can encapsulate or adsorb unmodified proteins and peptides (12)(13)(14), they can also induce immune responses to the material itself (15)(16)(17)(18)(19), or induce tolerance to antigens if a delivery material is used multiple times (20). Therefore, it is beneficial for vaccine formulations to minimize delivery of material that is not the target antigen.…”
Section: Introductionmentioning
confidence: 99%